REFINING VENT EMISSIONS FROM FINE DROPLET AEROSOLS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Vent emissions from industrial enterprises cause air pollution to a great extent. These emissions contain solid or liquid particles. it is necessary to install cleaning units for those particles. Existing methods of cleaning as applied to fine droplet aerosols have a number of limitations, especially within liquid disperse phase. This is why it is relevant to design highly-efficient cleaning units for vent emissions refining from droplet aerosols of sub-micron sizes. The research reveals the most important parameters for designing highly-efficient cleaning units for vent emissions refining from droplet aerosols. The authors designed a pilot plant and performed a series of experiments to define the optimal geometrical characteristics and modes of operation for cleaning units. These theoretical and experimental studies mase it possible to design three types of cleaning units with precipitating elements in the form of pipes and slotted channels with L/D = 250 dimensions.